Synergism between cryoablation and GM-CSF. Issue 6 (15th April 2015) - Xu, Hongchao; Wang, Qifu; Lin, Chunnan; Yin, Zhilin; He, Xiaozheng; Pan, Jun; Lu, Guohui; Zhang, Shizhong
<x xml:space="preserve">Abstract</x> Glioma is the most common malignant primary brain tumor, and it has a poor prognosis. Studies have shown that cryoablation can activate antitumor immunoeffects by promoting the augmentation of dendritic cells (DCs). Granulocyte macrophage colony-stimulating factor (GM-CSF) has been shown to be useful for immunotherapy against glioma because it can stimulate DCs to present tumor antigen. Previous studies have shown that cryoablation and GM-CSF can exert antitumor effects. To test the hypothesis that combined therapy with cryoablation and GM-CSF for glioma could synergistically improve specific antiglioma immunity in mice, we tested the validity of this assumption in a murine subcutaneous GL261 glioma model. C57BL/6 mice with subcutaneous GL261 glioma were created and divided into four groups: no treatment, GM-CSF injection, cryoablation treatment, and GM-CSF and cryoablation combined treatment (n=20 in each group). Serial immune indicators were detected at sequential time points during treatment. Compared with the other groups, in the combined treatment group, DCs were more activated and their numbers were markedly upregulated, the secretion of interferon-γ from Th1 cells of mice spleen was increased, and the cytolytic activity of CD8+ CTLs exerted a more significant cytotoxic effect on GL261 glioma cells (P<0.05 for all). Furthermore, these changes peaked on the 7th day after treatment, and then gradually reduced, until the 21st day; these changes were higher than those at pretreatment (P<0.05). It is concluded that combined therapy with argon–helium cryoablation and GM-CSF could synergistically enhance the activation of DCs and induce a robust tumor-specific immunologic response in glioma-bearing mice.